Capacidad de formación de biopelícula y limo en Staphylococcus que causan mastitis subclínica bovina en el estado Zulia-Venezuela - Valero-Leal Kutchynskaya; Rivera-Salazar Jhoandry; Briñez Wilfido; Paz América; Piña Eyilde; Ávila Yeiny; Colina López Gladis (Kasmera, 2017)
Abstract: A total of 79 S. aureus strains and 47 coagulase negative Staphylococcus (CNS) isolates from cow milk suffering subclinical mastitis were investigated for their ability to form biofilm as one of the most important virulence factors. Using Congo Red Agar method, 80% of S. aureus strains were slime producers, while in CNS was 32%. By microtiter plate method, 55%, 17%, and 28% of S. aureus isolates were strong, moderate, and weak biofilm producers, respectively, while in CNS the percentages were 43%, 17%, and 40%, respectively. All isolates were screened by Polymerase chain reaction (PCR) for amplification of intercellular adhesion gene A (icaA). In S. aureus isolates the icaA gene was present in 65 % while in CNS was 11%. The majority of S. aureus characterized in this study formed biofilm, which suggests that biofilm formation has an important role in the virulence of S. aureus isolated from bovine intramammary infections in Zulia state.